2011
DOI: 10.1603/ec10292
|View full text |Cite
|
Sign up to set email alerts
|

Control of Mushroom Sciarid Fly Lycoriella ingenua Populations With Insect Growth Regulators Applied by Soil Drench

Abstract: Mushroom sciarid fly Lycoriella ingenua (Dufour, 1839) comb. nov., is one of the most common fly pests affecting the cultivation of Agaricus bisporus (Lange) Imbach in Turkey. In this study, eight insect growth regulators (IGRs)--diflubenzuron, flufenoxuron, lufenuron, methoprene, novaluron, pyriproxyfen, teflubenzuron, and triflumuron-were tested for their potential to control L. ingenua populations in two successive growing periods. Treatments were targeted at larvae as soil drenches; treatment efficacy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
1
20
0
9
Order By: Relevance
“…버섯파리는 파리목(Diptera)에 속하는 곤충으로 크게 네 가지 그룹 또는 계통으로 분류되는데 세시드(Cecidomyiidae), 포리드(Phoridae), 마이세토필(Mycetophilidae), 그리고 시 아리드(Sciaridae)로 알려져 있다. 이러한 버섯파리들은 우리나라를 포함해 거의 세계 모든 나라에서 발생하여 지 속적인 문제를 발생시키는 해충이 되고 있다 (Wyatt, 1963;Clift, 1979;White, 1985;Kim and Hwang, 1996;Erler et al, 2011). 버섯파리는 우리나라 양송이뿐만 아니라 표고, 느타리 버섯 등에서 다량으로 발생하여 심각한 피해를 주고 있는 중요한 해충으로 알려져 있다 (Kim et al, 1999;Kim et al, 2012;Shin et al, 2012, Kwon et al, 2013.…”
Section: 서 론unclassified
“…버섯파리는 파리목(Diptera)에 속하는 곤충으로 크게 네 가지 그룹 또는 계통으로 분류되는데 세시드(Cecidomyiidae), 포리드(Phoridae), 마이세토필(Mycetophilidae), 그리고 시 아리드(Sciaridae)로 알려져 있다. 이러한 버섯파리들은 우리나라를 포함해 거의 세계 모든 나라에서 발생하여 지 속적인 문제를 발생시키는 해충이 되고 있다 (Wyatt, 1963;Clift, 1979;White, 1985;Kim and Hwang, 1996;Erler et al, 2011). 버섯파리는 우리나라 양송이뿐만 아니라 표고, 느타리 버섯 등에서 다량으로 발생하여 심각한 피해를 주고 있는 중요한 해충으로 알려져 있다 (Kim et al, 1999;Kim et al, 2012;Shin et al, 2012, Kwon et al, 2013.…”
Section: 서 론unclassified
“…L. ingenua es una plaga común en el cultivo de hongos y en invernaderos, la especie puede encontrarse también en suelos forestales y en áreas agrícolas (Mohring, et al, 2012). En el mundo L. ingenua es considerada una plaga importante en la producción del hongo A. bisporus (Erler et al, 2011;O´Connor y Keil, 2005;Shamshad et al, 2009;White et al, 2000). Esta especie se distribuyen en Asia (Japón y Korea), Europa (Polonia, Gran Bretaña), Norte América, México, Rusia, Turquía, Australia.…”
Section: Diagnosis De Bradysia Impatiensunclassified
“…Esta especie se distribuyen en Asia (Japón y Korea), Europa (Polonia, Gran Bretaña), Norte América, México, Rusia, Turquía, Australia. Probablemente L. ingenua tenga una distribución cosmopolita (Erler et al, 2011;Komarov, 2007;Lewandowski et al, 2004;Mohring, et al, 2012;Pérez et al, 2013;Shamshad et al, 2008;Shin, et al, 2012). Se recolectaron 48 adultos de L. ingenua de las cámaras de cría, De los cuales cuatro machos fueron procesados molecularmente; las secuencias genéticas fueron depositadas en el GenBank con número de acceso KP100538.…”
Section: Diagnosis De Bradysia Impatiensunclassified
See 1 more Smart Citation
“…Pyriproxyfen is active against a number of housefly, mosquito, and cockroach species and used as a feed‐through compound in poultry, cattle, and swine. In particular, it was suggested that pyriproxyfen could be used to control sciarid populations on mushrooms . The maximum residue limits were 0.5 mg/kg in cottonseed and citrus fruits and 1 mg/kg in tomato according to the Chinese national standard .…”
Section: Introductionmentioning
confidence: 99%